Metafora dalam Ungkapan yang Berkaitan dengan Hewan - Lasut, Theresia Conny (Universitas Sam Ratulangi, 2015)
Inthe social life the values are always bounded to the certain culture. Everymember of the society in one culture communicate by using the language. We cansee the important of the language in human life. Indonesia as a big countrypossessÂ Indonesian language as theofficial language but there are many local languages that exist in this region.One of the local language is Manadonese Malay. Theaim of this research is to find out the methapor meaning in the expression thatrelates to animal in Manadonese Malay. The method used was descriptivequalitative. The result showed that the way of using the methapor related tothe animal had eleven aspects. They are enemies, insulting, less in faith,fear, excessive want, careful, keep possesion, equality, excessive action,stupidity, and not caring.